Gingival metastasis from salivary duct carcinoma of the parotid gland - Bernabe, Daniel G. [UNESP]; Veronese, Luiz A.; Miyahara, Glauco Issamu [UNESP]; Conrado-Neto, Sebastiao [UNESP]; Biasoli, Eder Ricardo [UNESP] (Amer Acad Periodontology, 2008)
Background: This article reports a rare case of metastasis of salivary duct carcinoma of the parotid gland to the gingiva and reviews the occurrence of metastatic processes to the oral mucosa.Methods: A 67-year-old white male presented with a chief complaint of a painless nodular tissue growth on the gingiva with reportedly 5 months of evolution. The intraoral examination revealed a reddish, superflcially ulcerated nodular lesion (similar to 2 cm in diameter) on the right mandibular buccal attached gingiva, and the clinical aspect was that of a benign reactive lesion. The patient had undergone a parotidectomy for removal of a salivary duct carcinoma of the parotid gland almost 1 year before. A biopsy of the gingival lesion was performed, and the biopsied tissue was forwarded for histopathologic examination.Results: The analysis of the histopathologic sections of the gingival lesion revealed histomorphologic characteristics very similar to those of the primary parotid gland tumor. The definitive diagnosis was gingival metastasis from a salivary duct carcinoma of the parotid gland. The patient died of complications of a pulmonary metastasis I month after the diagnosis of the oral metastatic lesion.Conclusions: Gingival lesions that mimic reactive and hyperplastic lesions may be metastases from malignant neoplasias of diverse origins. An accurate and timely diagnosis is crucial to establish proper and immediate treatment of the metastatic tumor and possibly identify an occult primary malignant neoplasia.
Keywords: carcinoma; case report; gingiva; metastasis; parotid gland; salivary duct